Description and implementation: Power-Profile - Rice, T. (Rowing Australia, 2019)
Background Revised power-profile tests Frequency of the Power Profile Structure of the Power Profile Ergometer Drag Factors (Test Efforts 1-4) Power Profile Test Administration Preparation Power-Profile Test Administration (Test Efforts 1-4): 30 min ROPEN Test Administration Submission of ergometer test data Data Template Download Evaluation and implementation of the data How can the ergometer test battery assist with training prescription and modification?